The reality of social studies Teachers Awareness regarding the notion of augmented reality technology and the strategy of its usage in teaching to develop geographical phenomena from the social studies teachers perspectives - Alsanea, Zahraa Mohammed; Alawaidi, Afrah Hafez (Journal of Educational and Psychological Sciences, 2021)
The aim of the study was to learn about the use of augmented reality technology to understand and develop geographical phenomena from the point of view of social studies teachers. To achieve the objectives of the study the researchers have used a descriptive approach. An augmented reality questionnaire was applied using the augmented reality technology on a random sample consisting of sixty-six participants all of them are social studies teachers of both genders from Al-qunfudhah province, and in order to calculate the degree of use of augmented reality which was used by social studies teachers the arithmetic averages were used. The study presents the following results:The degree of reality in the use of augmented reality that social studies teachers have been used in Al-qunfudhah province, came in a high degree but close to average with an average arithmetic 2.09. As well as the degree of impediments in the use of augmented reality came in a high degree with an average arithmetic 2.40.In the light of the findings of the study researchers have recommended to stress the importance of the use of augmented reality technology in teaching and the need for drawing the attention of the ministry of education's officials to encourage and urge the teachers to use it,building computer-based educational programs based on augmented reality technology,work on overcoming the impediments that limits the use of augmented reality and its impact on both teaching and learning process.Besides achieving positive outcomes through using it.
Keywords: Augmented reality technology; Augmented reality impediments; geographical phenomena; social studies teachers